(untitled) (Economic and Political Thought, 2010)
The end of the era of communism in Poland initiated a period of enormous systematic changes which led to the establishment of democracy and introduction of market economy. The transformation of the economic system meant a thorough reform of the Polish economy through substitution of central planning by free market mechanisms. This caused changes not only in the sphere of production but also within the distribution of wealth and in the social sphere. The present article is intended to examine the influence of the economic transformation in Poland on the social sphere after 1989. As a research method it uses a theoretical analysis of selected publications and Internet resource materials. In the first part of the article the author presents the origin of the Polish systematic changes started in the late 1980s. Next the main areas of economic changes are characterized. In the final part of the article the author analyses social changes resulting from the introduced economic reforms.